Dental caries: a disease which remains a public health concern in the 21st century--the exploration of a breakthrough technology for caries prevention - Cummins, D (The Journal of clinical dentistry, 2013)
This paper provides an overview of modern concepts of dental caries, including its etiology, prevalence, and risk factors. The multifactorial nature of the disease is reviewed, and the concept of reducing caries initiation and progression by reducing pathological factors and restoring caries balance is discussed. In addition, the role and efficacy of fluoride in reducing and preventing caries is highlighted, demonstrating its successes and limitations. A novel technology, based upon arginine and an insoluble calcium compound, has been identified which targets dental plaque to prevent initiation and progression of the caries process by reducing pathological factors. As the mechanisms of action of arginine and fluoride are highly complementary, a next-generation dentifrice has been developed, which combines arginine, an insoluble calcium compound, and fluoride, and has been clinically proven to provide superior caries prevention.